The Effect of Service Quality on T-Cash Customer Satisfaction using System Dynamics Framework - Dhyna Octabriyantiningtyas; Erma Suryani (Journal of Information Systems Engineering and Business Intelligence, 2019)
Background: Every year, the number of T-Cash users is increasing significantly. However, the increase is not in sync with the number of T-Cash transactions. In this year, it was noted that active T-Cash users were only 35%. Some clinical studies have established an assessment of the quality of services, there are several dimensions assessed according to the topic of research. The dimensions of service quality used in this study are dimensions of efficiency, reliability, responsiveness, privacy, and security.Objective: This study aims to build general models and simulations in increasing customer satisfaction with the quality of T-Cash services and produce the best scenarios that can be used by policymakers in increasing customer satisfaction.Methods: System dynamics framework is utilized for the development of the model and scenarios. Because by using a system dynamics framework can predict service quality sometime in the future so that it can produce policies for the company.Results: The simulation results are considered valid because they produce E1 values of 3% (E1 valid when E1 ≤ 5%) and E2 of 7% (E2 valid when E2 ≤ 30%). E1 is mean comparison and E2 is error variance. Based on these 2 scenarios, a policy can be taken that scenario 1 significantly increases customer satisfaction compared to scenario 2.Conclusion: Based on the simulation that has been done, it can be concluded that the dimensions of responsiveness, privacy, reliability, security, and efficiency have an effect on improving service quality. On the scenario 1, it can be concluded that with the addition of the user friendliness dimension, the service quality will experience a significant increase over the next 5 years.